Aktivitas Peredaman Ekstrak Daun Pandan Wangi (Pandanus amaryllifolius) dengan Metode DPPH (2,2-difenil-1-pikrilhidrazil) - Nurhasanah, Devika; Nofran Putra Pratama; Sri Purwa Pujihastuti (JOURNAL OF PHARMACEUTICAL (JOP), 2023)
Background: Antioxidants are compounds that prevent an oxidation reaction from free radical compounds and important role in capturing free radicals in the human body. Excessive free radicals in the body can cause tissue damage and degenerative diseases. Pandanus amarillyfolius are known to act as natural antioxidant that have the potential to capture free radical compounds, because of their presence of flavonoid compounds. Objective: This study aims to determine the free radical scavenging activity of DPPH against the leaf extract of Pandanus amaryllifolius. Method: Pandanus amaryllifolius extraction was carried out using the maceration method with methanol as solvent (1:10). Concentration was carried out using a rotary evaporator to obtain a thick extract. Phytochemical screening and TLC test were carried out qualitatively using the mobile phase n-butanol: acetic acid: water (6:2:2) and phytochemical testing including flavonoids, alkaloids, saponins, tannins, steroids or terpenoids to determine the presence of flavonoid compounds as antioxidants. Free radical scavenging activity was tested using DPPH free radical scavenger with concentrations of vitamin C 2, 4, 5, 6, 8 ppm and pandanus fragrance extract concentrations of 10, 15, 20, 25 ppm and measured using a UV-Vis spectrophotometer to calculate the IC50 value. Result: The results of the phytochemical screening test of fragrant pandan indicate the presence of flavonoid compounds. The Rf value of the TLC test obtained 0.765 quarcetin and 0.787 extract and the resulting yellow spots, the Rf value of pandan extract which was almost the same as the Rf value of quercetin indicated that the pandan extract may contain the same compounds as quercetin, namely flavonoid compounds. The results of the free radical scavenging activity of methanol extract of pandan leaves were 86,861 g/ml and for comparison, vitamin C was 39,103 g/ml. Based on the statistical analysis of the T-Test, it is known that there is a difference between the sample and the standard with a significant value (p <0.05), namely 0.001 and 0.023. Conclusion: The Pandanus amaryllifolius extract test using the DPPH method is in the strong category (IC50 <50 -100 g/ml) and the comparison of Vitamin C is in the very strong category (IC50 <50 g/ml).